Spatial Planning to Improve the Quality of the Housing Environment based on an Assessment of Residents’ Satisfaction; Case Study Hesa Mehr Housing, Pardis New Town - Reza Rezaei Khaboushan; Marjan A. Nemati Mehr (صفه)
The present study seeks to discover the factors influencing the quality of the housing environment and propose strategies to improve quality in the case study, Mehr housing named Hesa in Pardis New Town. Housing environment quality is dynamic, complex, and multidimensional, comprised of various physical, social, economic, and environmental aspects, which can affect resident satisfaction. The nature of the research is qualitative but due to the extraction of measurable criteria and a combination of methods quantitative measurements are used in the form of correlation methods. Employing structural equations, the formative factors of housing environment quality were measured as independent variables, and satisfaction was measured as a dependent variable. The results indicate a dissatisfaction with the safety and environmental aspects of the residential environment, and with the facilities and physical characteristics of the residential unit in Hesa project. They also indicate the importance of social and environmental issues at neighbourhood scale and the physical quality of residential unit at architecture scale. Based on results, strategies for improving the quality of the environment were developed using the AIDA technique. Using the analysis technique of decision-making areas, AIDA, different scenarios of improving the quality of the residential environment are presented, followed by an evaluation of them, resulting in the selection of the scenario which strategy is the centralised development of public welfare services and leisure providers as well as the development of roads and infrastructure (sewerage system, etc.), improving the quality of the residential unit and environmental safety.